KEDUDUKAN PENDIDIK DALAM PERSPEKTIF ISLAM MENURUT AKRIM DALAM BUKU ILMU PENDIDIKAN ISLAM - Fatimatus Zahrah; Ode Mohamad Man Arfa Ladamay (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
The background of this research is that educators do not only teach in that academic field, but are also required to have noble morals. But in the context of islamic eduaction, educators are known as murabbi, mu”allim, mudarris, and murshid. The position of an educator becomes a light in life in the world, especialli in the hereafter. In the context of islamic education, the position of an educator is very important. The type of reserch used is library researc and uses descriptive methods as data analysis techniques. The results of the study are that there are quite a lot of requirements to be fulfilled by educators indicating that the responsibilities and duties of educators are indeed heavy. However, it is pricesely because of that the he gets a very high position. The position of an educator as well as a parent is a position that he must do.